Effect of physiological fluid on the photothermal properties of gold nanostructured - Amézaga González, María Fernanda; Farias, Rurik; Chapa, Christian; Avila Orta, Caros; Garcia Casillas, Perla Elvia (2023)
https://www.mdpi.com/1422-0067/24/9/8339